Reforming Administrative Procedures in the Tourism, Food and Road Transportation Sectors in Bulgaria - World Bank; Ministry of Economy and Energy of Bulgaria (World Bank, Washington, DC, 2013)
The results of the alpha survey on administrative barriers completed in 2006 indicate that, notwithstanding recent government reforms to reduce regulations affecting firms, administrative burdens are still substantial impediments to doing business. Based on the survey, the Bulgarian Government has commissioned an in-depth analysis of the procedure affecting three sectors: tourism, food, and transport. This report recommends the efficiency of inspections should be evaluated and a centralized inspection authority for foodstuffs and feed should be considered. More work is needed to assess the efficiency of the current inspection service.